Multidimensional assessment of a patient with perinatally diagnosed multiaxis - a case study - Agata Bloch; Anna Złotnik; Krystian Kałużny; Magdalena Hagner-Derengowska; Anna Kałużna; Walery Żukow (Kazimierz Wielki University, 2018)
Introduction: For many years, congenital defects have been of particular interest to epidemiologists, neonatologists and paediatricians. Their incidence is still increasing, and the types are constantly being modified. Well-prepared prenatal tests allow for their early detection and if possible, these defects are operated during fetal life. Unfortunately, a significant proportion of cases do not qualify for these treatments. Then, a child with a defect or congenital malformation syndromes may undergo surgery only after birth. This often results in a delay in neurophysiological development, and in an extreme case also in the mental state. The aim of this study was to test a multidimensional assessment of a child who was diagnosed with numerous congenital malformations perinatally. After combining the elementary auxiliary diagnostics of the boy with pediatric norms, he tried to assess his general physical fitness by carrying out a Wrocław test of general physical fitness for pre-school children prepared by B. Sekita. We also analyzed selected practical tests for the integration of dynamic and postural reflexes developed by S. Masgutova and N. Akhmatova. Results: The results of selected anthropometric measurements of the patient are definitely lower than those in parallel, despite normal birth parameters. The overall physical fitness of the boy is sufficient. The integration of selected dynamic and structural reflexes is correct. He was diagnosed with a problem of motor coordination in the area of body bias. Summation: Immediate and comprehensive care from a team of specialists increases the chances of survival and optimal development of a child with serious congenital malformations. Early and systematic rehabilitation of the patient is a necessary condition to obtain effects in the convalescence process and its optimal neurophysiological development.